2013
DOI: 10.1007/s10342-013-0701-6
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new procedure to estimate the carbon stocks of all forest pools and impact assessment of methodological choices on the estimates

Abstract: Forest ecosystems play a major role in atmospheric carbon sequestration and emission. Comparable organic carbon stock estimates at temporal and spatial scales for all forest pools are needed for scientific investigations and political purposes. Therefore, we developed a new carbon stock (CS) estimation procedure that combines forest inventory and soil and litter geodatabases at a regional scale (southern Belgium). This procedure can be implemented in other regions and countries on condition that available exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
1
6
0
1
Order By: Relevance
“…As for the carbon concentration, many studies have for convenience used a fixed value (e.g. 50%) of mass as carbon in both biomass and necromass (Brienen et al, 2015;Chao et al, 2009;Coomes et al, 2002;Latte et al, 2013). We found that carbon concentration decreased markedly with decay classes (Table 2; Fig.…”
Section: Wood Density and Carbon Concentration Among Decay Classessupporting
confidence: 49%
See 2 more Smart Citations
“…As for the carbon concentration, many studies have for convenience used a fixed value (e.g. 50%) of mass as carbon in both biomass and necromass (Brienen et al, 2015;Chao et al, 2009;Coomes et al, 2002;Latte et al, 2013). We found that carbon concentration decreased markedly with decay classes (Table 2; Fig.…”
Section: Wood Density and Carbon Concentration Among Decay Classessupporting
confidence: 49%
“…Converting volume to carbon requires knowing both wood density and carbon concentration (IPCC, 2006;Latte et al, 2013;Weggler et al, 2012). Our study found that both wood density and carbon concentration decline significantly with the class of decay (Fig.…”
Section: Wood Density and Carbon Concentration Among Decay Classesmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, to disentangle the specific 52 warming effect of water availability on beech, it seems more appropriate to sample trees from 53 stands with optimal growing conditions. Changes in temperature thresholds in these stands 54 might play a major role in influencing carbon stock (Latte et al, 2013) Since the 1990s, anomalies in beech health (e.g., worsening crown conditions) have been 58 observed throughout Europe (UNECE, 2005) and in Belgium (Laurent and Lecomte, 2007). 59…”
mentioning
confidence: 99%
“…(2) and (3) to determine the AGB and RB of saplings (1 cm ≤ DBH < 10 cm) and dead standing trees. To correct for the fact that part of the mass in dead trees is already decomposed, we used a correction factor based on visual assessment of decomposition state: 1 for dead trees with no signs of decomposition, 0.75 for moderately decomposed trees and 0.5 for highly decomposed trees (Latte et al 2013). …”
Section: Methodsmentioning
confidence: 99%